2017
DOI: 10.1016/j.dsx.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic syndrome and osteoarthritis: The Fasa Osteoarthritis Study

Abstract: Our findings revealed that metabolic markers are strongly associated with OA and the addition of each component of the MeS, significantly increases the risk of developing OA, therefore control of metabolic factors and appropriate screening must be considered in health policy making and prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
4
18
3
Order By: Relevance
“…This study did not account for sampling weights in the statistical analysis, even though the study, a nationwide survey, had a stratified, multistage probability sampling design. Contrary to other literature, the small Fasa Osteoarthritis Study showed that the odds ratio between MetS and OA paradoxically increased from 6.8 to 10.9 after adjusting for age, sex, and BMI .…”
Section: Resultscontrasting
confidence: 96%
See 3 more Smart Citations
“…This study did not account for sampling weights in the statistical analysis, even though the study, a nationwide survey, had a stratified, multistage probability sampling design. Contrary to other literature, the small Fasa Osteoarthritis Study showed that the odds ratio between MetS and OA paradoxically increased from 6.8 to 10.9 after adjusting for age, sex, and BMI .…”
Section: Resultscontrasting
confidence: 96%
“…In the Fasa Osteoarthritis Study, the odds ratio paradoxically increased from 6.8 to 10.9 after adjustment for age, sex, and BMI . Despite consistent findings from the literature that age is a strong risk factor for OA, this study showed a paradoxically reduced risk of OA with advanced age .…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…After Puenpatom and Victor (2009) have suggested for the first time that MeS may be associated with OA, multiple studies have documented a relationship between OA and MeS components (Askari et al 2016), which have led to the introduction of the term of metabolic OA (Courties et al 2017). Our findings support the notion that a metabolic factor (or factors), independent from weight, is part of the pathogenesis of OA (Askari et al 2017b).…”
Section: Discussionsupporting
confidence: 80%